2016
DOI: 10.1002/smr.1800
|View full text |Cite
|
Sign up to set email alerts
|

Searching crowd knowledge to recommend solutions for API usage tasks

Abstract: Stack Overflow (SO) is a question and answer service directed to issues related to software development. In SO, developers post questions related to a programming topic and other members of the site can provide answers to help them. The information available on this type of service is also known as 'crowd knowledge' and currently is one important trend in supporting activities related to software development.We present an approach that makes use of 'crowd knowledge' in SO to recommend information that can assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 41 publications
(58 reference statements)
0
16
0
Order By: Relevance
“…Additionally, there could be more efficient ways to seek information about a specific problem as, for example, searching with Google, the Stack Overflow search engine, or even using recommendation approaches that use Stack Overflow data [40,41,24]. We advocate that due to its browsing nature, cookbooks can be complementary to searching mechanisms.…”
Section: Rq #5mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there could be more efficient ways to seek information about a specific problem as, for example, searching with Google, the Stack Overflow search engine, or even using recommendation approaches that use Stack Overflow data [40,41,24]. We advocate that due to its browsing nature, cookbooks can be complementary to searching mechanisms.…”
Section: Rq #5mentioning
confidence: 99%
“…For instance, in a searching process, a developer would be able to write a query, and a system would bring from Stack Overflow the best results for such query. Such searching process goes in the direction of automated on-demand developer documentation [23] with recommendation systems, and a system of this type using Stack Overflow content is presented in [24]. On the other hand, a crowd cookbook could, for instance, be used by someone who wants to know what are the main themes of an API, which is specially useful for newcomers.…”
Section: Introductionmentioning
confidence: 99%
“…Literature has also analyzed SO in context of mobile development [18]. Campos et al [19] uses the criterion of text based matching to find a potential programming question for a user to answer. Moreover, work has gone deeper and has found that high reputation users are efficient in providing good answers [20,21].…”
Section: Related Workmentioning
confidence: 99%
“…We could not reuse the classifier built by Souza et al [7] and Campos et al [14], as this classifier does not address debug-corrective questions. Also the classifier built by Campos and Maia [15] does not focus only on how-to-doit and debug-corrective.…”
Section: Automatic Classification Of Questionsmentioning
confidence: 99%
“…For Swing, 50% of the covered elements are covered by numbers of threads in the interval [1,8], and for Android in the interval [1,14], i.e., a large part of the covered elements are not related to a very large number of threads.…”
Section: How-to-do-it Coverage Of Api Elementsmentioning
confidence: 99%